2007
DOI: 10.1248/bpb.30.2207
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones from the Seeds of Cassia tora with Inhibitory Activity on Protein Glycation and Aldose Reductase

Abstract: Nine anthraquinones, aurantio-obtusin (1), chryso-obtusin (2), obtusin (3), chryso-obtusin-2-O-b b-D-glucoside (4), physcion (5), emodin (6), chrysophanol (7), obtusifolin (8), and obtusifolin-2-O-b b-D-glucoside (9), isolated from an EtOAc-soluble extract of the seeds of Cassia tora, were subjected to in vitro bioassays to evaluate their inhibitory activity against advanced glycation end products (AGEs) formation and rat lens aldose reductase (RLAR). Among the isolates, compounds 6 and 8 exhibited a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 29 publications
6
40
0
Order By: Relevance
“…3). The present biological data and our previous results on anthraquinones from Cassia tora and Rumex japonicus (Jang et al, 2007;Kim et al, 2008) demonstrated that anthraquinones having 6-hydroxyl group show strong AR inhibitory activity, and 6-hydroxyl and/or 1-hyroxyl groups of anthraquinones contribute to inhibitory activity on AGEs formation. This is the first report of compounds 1, 2, 5, 7, and 8 having inhibitory activity on AGEs formation or RLAR.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…3). The present biological data and our previous results on anthraquinones from Cassia tora and Rumex japonicus (Jang et al, 2007;Kim et al, 2008) demonstrated that anthraquinones having 6-hydroxyl group show strong AR inhibitory activity, and 6-hydroxyl and/or 1-hyroxyl groups of anthraquinones contribute to inhibitory activity on AGEs formation. This is the first report of compounds 1, 2, 5, 7, and 8 having inhibitory activity on AGEs formation or RLAR.…”
Section: Resultssupporting
confidence: 81%
“…In our ongoing project directed toward the discovery of preventive agents for diabetic complications from herbal medicines (Yoo et al, 2008;Jang et al, 2007), the roots of Knoxia valerianoides Thovel ex Pitards (Rubiaceae) were chosen for more detailed investigation, since the EtOAc-and n-BuOH-soluble fractions of the MeOH extract showed significant in vitro inhibitory activities on both AGEs formation and rat lens aldose reductase (RLAR). The roots of K. valerianoides (Radix Euphorbiae seu Knoxiae) are famous in traditional medicine in Asia, and have been used for relatively moderate fluid accumulation in the chest and flanks with such symptoms as labored breathing, dull pain in the lateral aspect of the chest, expectoration of thick sputum, and a thick, greasy tongue moss (Bensky and Gamble, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In our ongoing project directed toward the discovery of preventive agents for diabetic complications from herbal medicines (Jang et al, 2007), the flowers of E. annuus were chosen for more detailed investigation. The ethyl acetate-soluble extract was found to inhibit both the formation of AGEs and rat lens aldose reductase (RLAR) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies identified several single compounds and extracts from natural products that inhibited AGE formation. 18,[20][21][22] To identify agents that disrupt AGE-induced protein crosslinking in vitro, candidate compounds were added to a collagen-coated surface that had been pretreated with AGE-BSA; AGE-collagen cross linking was detected using specific anti-AGE and horseradish peroxidase-linked antibodies. The AGE cross-linking disruptor N-phenacylthiazolium bromide (PTB) reacts with and cleaves covalent AGE-derived protein crosslinks.…”
Section: Discussionmentioning
confidence: 99%